Laterally Aggregated Polyacrylamide Gels for Immunoprobed Isoelectric Focusing - Jeeawoody, Shaheen (Anal Chem, 2020)
Immunoprobed isoelectric focusing (IEF) resolves proteins based on differences in isoelectric point (pI) and then identifies protein targets through immunoprobing of IEF-separated proteins that have been immobilized onto a gel scaffold. During the IEF stage, the gel functions as an anti-convective medium and not as a molecular sieving matrix. During the immunoprobing stage, the gel acts as an immobilization scaffold for IEF-focused proteins via photoactive moieties. Here, we characterized the effect of gel pore size on IEF separation and in-gel immunoassay performance. We modulated polyacrylamide (PA) gel pore size via lateral chain aggregation initiated by PEG monomers. During IEF, the 2% PEG highly porous PA gel formulation offered higher resolution (minimum pI difference ~0.07 ± 0.02) than unmodified 6%T, 3.3%C (benchmark) and 6%T, 8%C (negative control) PA gels. The highly porous gels supported a pH gradient with slope and linearity comparable to benchmark gels. The partition coefficient for antibodies into the highly porous gels (K = 0.35 ± 0.02) was greater than the benchmark (3×) and negative control (1.75×) gels. The highly porous gels also had lower immunoassay background signal than the benchmark (2×) and negative control (3×) gels. Taken together, lateral aggregation creates PA gels that are suitable for both IEF and subsequent in-gel immunoprobing by mitigating immunoprobe exclusion from the gels while facilitating removal of unbound immunoprobe.